Evaluation of possible prostate displacement induced by pressure applied during transabdominal ultrasound image acquisition - Dobler, Barbara; Mai, Sabine; Rossier, Christine; Wolff, Dirk; Wertz, Hansjörg; Lohr, Frank; Wenz, Frederik (Strahlentherapie und Onkologie, 2006)
Background and Purpose: For accurate positioning of the prostate in external radiotherapy, transabdominal ultrasound Localization and positioning systems are available. Reports have stated that probe pressure applied during image acquisition causes clinically relevant prostate displacement. The aim of this study was to investigate the prostate displacement due to the pressure applied during transabdominal ultrasound image acquisition with the BAT((R)) ultrasound system. Material and Methods: For ten patients who had undergone iodine-125 seed implantation for brachytherapy of prostate cancer, X-ray simulations were performed before and during ultrasound image acquisition. The iodine seeds are visible on the X-ray images, representing the position of the prostate. The simulator's crosshair, indicating the isocenter, was used as reference coordinate system. For each patient the change in prostate position was calculated based on the seed positions during and after ultrasound examination. Results: A maximum displacement of the prostate of 2.3 mm in anteroposterior and 1.9 mm in craniocaudal direction and a rotational change of up to 2.5 degrees were observed. If the system was not handled correctly and too much pressure was applied, a shift of the prostate of up to 10 mm could be induced. Conclusion: Compared to the prostate displacement due to changes in rectal filling, which according to Crook et al. can be as much as 1.7 cm, the maximum displacement of Less than 0.3 cm caused by the probe pressure is negligible. However, proper education of the staff and preparation of the patient are essential for the safe use of the system.